Cluster analysis for the overall health status of elderly, multimorbid patients with diabetes - Bing, Yan; Yuan, Lei; Liu, Ji; Wang, Zezhong; Chen, Lifu; Sun, Jinhai; Liu, Lijuan (Frontiers in Public Health, 2023)
Purpose: To evaluate the overall health status and health-related abilities and problems of elderly patients with diabetes and multimorbidity compared with those with diabetes only. Additionally, we aimed to identify different subgroups of elderly, multimorbid patients with diabetes. Methods: This cross-sectional study included 538 elderly patients with diabetes. The participants completed a series of questionnaires on self-rated health (SRH), diabetes self-management, self-efficacy, health literacy, depression, and diabetes distress. Differences in health-related abilities and problems were compared between elderly patients with diabetes and multimorbidity and those with diabetes only, with adjustments for covariates using propensity score matching. A cluster analysis was also performed to identify the overall health status subgroups of elderly, multimorbid patients with diabetes. Additionally, we conducted a multinomial logistic regression analysis to examine the predictors of health-related abilities and problem-cluster group membership. Results: Elderly patients with diabetes and multimorbidity experienced more health-related abilities and problems than those with diabetes only, particularly within the domains of depression (P＜0.001), diabetes distress (P＜0.001), and SRH (P=0.034). The level of health literacy in elderly, multimorbid patients with diabetes was also significantly higher than that in elderly patients with diabetes only (P＜0.001). Cluster analysis of elderly, multimorbid patients with diabetes revealed three distinct overall health status clusters. Multinomial logistic regression analysis indicated that age (OR=1.170, P=0.043), sex (OR=0.503, P=0.024), living situation (OR=2.769, P=0.011), BMI (OR=0.838, P=0.034), regular exercise (OR=2.912, P=0.041 in poor vs good; OR=3.510, P<0.001 in intermediate vs good), and cerebral infarction (OR=26.280, P<0.001) independently and significantly predicted cluster membership. Conclusion: Compared with elderly patients with diabetes only, those with diabetes and multimorbidity experienced more health-related abilities and problems within the domains of SRH, depression, and diabetes distress. Additionally, the level of health literacy in elderly, multimorbid patients with diabetes was significantly higher than that in those with diabetes only. Among the multimorbid diabetes group, old age, male sex, living without a partner, slightly lower BMIs, not exercising regularly, and experiencing cerebral infarctions were all positively correlated with worse overall health status.